Determinants of Emerging Market Sovereign Bond Spreads : Fundamentals vs Financial Stress - Petrova, Iva (IMF Working Papers; Working Paper ;, 2010)
This paper analyses the determimants of emerging market sovereign bond spreads by examining the short and long-run effects of fundamental (macroeconomic) and temporary (financial market) factors on these spreads. During the current global financial and economic crisis, sovereign bond spreads widened dramatically for both developed and emerging market economies. This deterioration has widely been attributed to rapidly growing public debts and balance sheet risks. Our results indicate that in the long run, fundamentals are significant determinants of emerging market sovereign bond spreads, while in the short run, financial volatility is a more important determinant of sperads than fundamentals indicators.